Molecular Pathogenesis, Tumor Microenvironment and Health Disparities in Select Pediatric Solid Tumors: An Integrative Narrative Review - MiaSara Pérez-Salvá; Carolyn M. Ruiz-Pérez; Alondra Veloz-Bonilla; Rocío K. Rivera-Valentín (Diseases, 2026)
Background/Objectives: Pediatric solid tumors (PST) are a biologically distinct group of malignancies whose developmental origins and molecular drivers differ substantially from those of adult cancers, with direct implications for therapeutic strategy and clinical outcome. This review synthesizes current evidence on molecular pathogenesis, tumor microenvironment biology, and the structural conditions that shape access to care across select PST. Methods: A narrative review of peer-reviewed literature was conducted primarily using PubMed, supplemented by Google Scholar, covering publications from 2000 to 2025. Tumor types were selected based on their prevalence in the pediatric population and the availability of evidence addressing both molecular features and health disparities. Body: Across eight tumor types (neuroblastoma, Ewing sarcoma, pediatric brain tumors, rhabdomyosarcoma, Wilms tumor, retinoblastoma, osteosarcoma, and chondrosarcoma), recurrent molecular alterations including MYCN amplification, EWS-FLI1 fusions, PAX-FOXO1 rearrangements and IDH 1/2 mutations emerge as central determinants of disease behavior and eligibility for treatment. The tumor microenvironment manifests as a shared mediator of immune exclusion and therapeutic resistance across tumor types, with, but not limited to, tumor-associated macrophages, myeloid-derived suppressor cells, and checkpoint molecule expression, identified as recurrent features influencing treatment response. Immunotherapeutic strategies have shown variable efficacy across PST, with the most consistent clinical benefit established in neuroblastoma. A critical and underappreciated pattern stands out across tumor types: children carrying the most aggressive molecular subtypes are disproportionately those with the least access to therapies those subtypes demand, emphasizing an overlap of biological and structural disadvantage that is also amplified in low- and middle-income countries, where late-stage presentation, treatment abandonment and limited access to molecular diagnostics compound the biological disadvantage. Conclusions: Within the eight PST reviewed, the most aggressive molecular subtypes and the greatest structural disadvantages converge in the same children; those carrying MYCN amplification, PAX-FOXO1 fusions, or EWS-FLI1 fusions are disproportionately those with the least access to the therapies their biology demands. Genomic and immunologic advances will only reach their full clinical potential when paired with inclusive trial data, diversified genomic databases, and most importantly, equitable access to biomarker-specialized therapies across all populations.